PENINGKATAN PENGETAHUAN SISWA MKI TERHADAP PENYELESAIAN SIKLUS AKUNTANSI PERUSAHAAN JASA - Henny Henny; Billy Prasetya; Riki Yanto (PROSIDING SERINA, 2021)
Mahkota Kasih Insani (MKI) Learning House is a learning house founded by Mrs. Sofia with the idea of helping students who cannot afford to go to school, starting from students who should attend Kindergarten, Elementary and Junior High Schools, as well as Vocational High Schools.  Especially for Vocational High School students need additional education in accounting so that the education of these students can run smoothly.  To prepare Vocational High School students who have just entered school, it is necessary to prepare for exams in the field of accounting by collaborating with lecturers and students from the Accounting Department, Faculty of Economics and Business, Universitas Tarumanagara about the training materials needed for these MKI students. The purpose of this community service activity is to increase the knowledge of MKI students towards the completion of the accounting cycle of service companies. The method used in this activity is an offline training method. The activity was carried out on Saturday, November 6, 2021 offline, namely coming to partner locations to provide training and still following strict health protocols. This community service activity starts from training on the completion of the service company's accounting cycle, including the financial statements of the service company, exercises on the completion of the service company's accounting cycle, questions and answers, and evaluation of community service activities. The implementation of community service activities can be concluded running smoothly, students actively ask questions and always answer practice questions correctly. Based on the evaluation results obtained from these students that they really appreciate the support from Universitas Tarumanagara in helping them improve their knowledge, so they can easily learn the completion of the service company's accounting cycle.